ANALISIS POTENSI KENDALA INFRASTRUKTUR PANTAI BATU KARAS SEBAGAI DESTINASI WISATA DI KABUPATEN PANGANDARAN - elma anggara; Nurmayadi, Dicky (JITSi : Jurnal Ilmiah Teknik Sipil, 2023)
Abstract— Infrastructure of the facilities available at the tourist attractions should be adequate as it will affect the comfort of visitors. However, there are still many tourist attractions in the district of Pangandaran that are still not adequate, one of them is the lack of temporary garbage disposal facilities and a lot of infrastructure due to the tourist attraction of the Karas Stone Beach which is said to be unsuitable for use and requires development and repair. The study aims to assess the viability of Karas Stone infrastructure as a tourist attraction in Pangandaran. Methods to conduct this research with qualitative descriptive techniques to determine how much the degree of infrastructure viability in Batu Karas as a tourist attraction in Pangandaran District. The sampling process is random (probability sampling), then the data that has been evaluated is then presented in the Table of Accessibility of Respondents (TCR). Data is collected through transportation, observations, interviews, and documentation. From the overall results of the Accessibility Level of Responds (TCR) of the tourist infrastructure of Batu Karas coast according to tourists obtained a score of 72.2% that falls into sufficient category, and changes are necessary to infrastructure to meet the goals and expectations in the future. The state of the Karas Stone Coast is not adequate because the local government has not undertaken development. Keywords — Batu Karas Beach, Infrastructure, tourist. Abstrak— Infrastruktur fasilitas yang ada pada objek wisata harus memadai karena akan berpengaruh pada kenyamanan pengunjung. Akan tetapi masih banyak objek wisata di Kabupaten Pangandaran yang masih belum memadai, salah satunya adalah kurangnya fasilitas tempat pembuangan sampah sementara dan banyaknya infrastruktur dikawasan objek wisata Pantai Batu Karas yang terbilang sudah tidak layak untuk digunakan sehingga membutuhkan pengembangan dan perbaikan. Studi ini bertujuan untuk mengevaluasi kelayakan infrastruktur Batu Karas sebagai tempat wisata di Pangandaran. Metode untuk melakukan penelitian ini dengan metode deskriptif kualitatif untuk mengetahui sejauh mana tingkat kelayakan infrastruktur di Batu Karas sebagai tempat wisata di Kabupaten Pangandaran. Proses pengambilan sampelnya dilakukan secara acak (probability sampling), lalu data yang telah dievaluasi kemudian disajikan dalam tabel Tingkat Capaian Responden (TCR). Data dikumpulkan melalui angket, observasi, wawancara, dan dokumentasi. Dari hasil keseluruhan Tingkat Capaian Responden (TCR) kelayakan infrastruktur wisata pantai Batu Karas menurut wisatawan didapatkan nilai 72,2% yang masuk ke kategori cukup, dan perubahan sangat diperlukan supaya infrastruktur memenuhi tujuan dan antisipasi mendatang. Keadaan prasarana Pantai Batu Karas belum memadai karena pemerintah daerah belum melakukan pengembangan. Kata kunci —  Pantai Batu Karas, Infrastruktur, Pariwisata